Plant Classification Knowledge and Misconceptions among University Students in Morocco - Lhoussaine Maskour; Anouar Alami; Moncef Zaki; Boujemaa Agorram (MDPI AG, 2019)
This study aims to assess learning outcomes and identify students’ misconceptions in plant classification. We conducted a questionnaire survey with undergraduate and master’s students. The qualitative analysis of the students’ responses made it possible to shed light on the difficulties of assimilation of many notions and also to identify the different misconceptions constructed during their learning courses about plant organisms. The findings indicate that some students are not motivated to take the course on plant classification. This demotivation is reinforced further by students’ perceptions of plant classification, especially that it is not important and not useful for learning other biology specialities. The findings also show that more than half of the students who participated in this study consider plant systematics a difficult subject. We also note that some of the students surveyed seem not to have acquired many concepts of plant biology including concepts related to the biology, reproduction and evolution of plants. Thanks to this, we could see different types of problems in plant classification, which constitute misconceptions hindering learning. Initial training in plant biology does not appear to have a significant effect in modifying students’ misconceptions related to plant classification.